SNIIC: a plataforma digital de cultura brasileira sob a perspectiva das convergências entre o Design e a Ciência da Informação - Silva, Anahi Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The National System of Information and Cultural Indicators (SNIIC) is a digital platform created by the federal government as a tool for the National Culture Plan, with the aim to map and aggregate in a single database, information related to Brazilian culture. It is a dynamic environment information that meets complex system characteristics, convergent, hybrid, and that presents great challenges for its implementation and enforcement. In this sense we propose to analyze the SNIIC from the perspectives of Information Science and Information Design establishing the general objective of identifying resources and subsidies that increase the possibilities of access, sharing and appropriation of information. The research is classified as literature, exploratory, theoretical and applied, since it starts from a literature survey in order to understand and contextualize the information systems and cultural indicators and thus outlining the problem; It is exploratory because it has the platform itself as an object for data collection, research and analysis; theoretical and applied, it aims to establish a product / service to improve the system of search and information retrieval. The test results confirmed the great potential of the platform, but had some problems, such as deficiencies in documentary production and search and information retrieval system. The first pointed problem can be fixed with archival policy adoption and digital curation, with methods and procedures related to the processing of electronic archival documents to correct these deficiencies in document production; already with respect to the second, indicate the practical application of a thesaurus on converted the model Simple Knowledge Organization System (SKOS) standard Resouce Description Framework (RDF), with a view to the organization, retrieval and interoperability between different information and Semantic Web systems, allowing the user to perform queries using their vocabulary in common use, thus providing greater accessibility to information maintained by SNIIC.

O Sistema Nacional de Informações e Indicadores Cultural (SNIIC) é uma plataforma digital criada pelo governo federal como instrumento para o Plano Nacional de Cultura, com o objetivo de mapear e agregar, em base de dados única, informações referentes à cultura brasileira. Trata-se de um ambiente dinâmico de informações que reúne características de sistema complexo, convergente, híbrido, e que apresenta grandes desafios para sua implementação e execução. Nesse sentido nos propomos a analisar o SNIIC sob as perspectivas da Ciência da Informação e do Design da Informação, estabelecendo como objetivo geral identificar recursos e subsídios que ampliem as possibilidades de acesso, compartilhamento e apropriação da informação. A pesquisa é classificada como bibliográfica, exploratória, teórico-aplicada, uma vez que se dá a partir de um levantamento bibliográfico com intuito de conhecer e contextualizar os sistemas de informações e indicadores culturais e assim delinear o problema; é exploratória porque tem a própria plataforma como objeto para coleta dos dados, estudo e análise; teórico-aplicada, pois visa estabelecimento de um produto/serviço para melhorar o sistema de busca e recuperação da informação. Os resultados da análise confirmaram o grande potencial da plataforma, mas revelaram algumas dificuldades, tais como: deficiências na produção documental e no sistema de busca e recuperação da informação. O primeiro problema apontado pode ser corrigido com a adoção política arquivística e curadoria digital, com métodos e procedimentos relacionados ao tratamento de documentos arquivísticos eletrônicos que corrijam estas deficiências na produção documental; já com relação ao segundo, indicamos a aplicação prática de um tesauro sobre convertido no modelo Simple Knowledge Organization System (SKOS) em padrão Resouce Description Framework (RDF), com vistas à organização, recuperação e interoperabilidade entre diferentes sistemas de informação e Web Semântica, permitindo que o usuário realize consultas utilizando seu vocabulário de comum uso, provendo assim uma maior acessibilidade às informações mantidas pelo SNIIC.
SNIIC: the digital platform of Brazilian culture from the perspective the convergences between the Design and Information Science
Keywords: Information Science; Information Design; Languages of convergences; National System of Information and Cultural Indicators; Digital Curation of Culture; Ciência da Informação; Design da Informação; Convergências de linguagens; Sistema Nacional de Informações e Indicadores Culturais